2019
DOI: 10.1108/ijlm-12-2017-0338
|View full text |Cite
|
Sign up to set email alerts
|

Service modularity in managing healthcare logistics

Abstract: Purpose The purpose of this paper is to examine how modularity is used for enabling value creation in managing healthcare logistics services. Design/methodology/approach Material logistics of four different kinds of hospitals is examined through a qualitative case study. The theoretical framework builds on the literature on healthcare logistics, service modularity and value creation. Findings The case hospitals have developed their material logistics independently from others when looking at the modularity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…A cross-section of some key logistics key variables or factors are presented in Table II. [23], examined how modularity is used for enabling value creation in managing healthcare logistics services. They applied materials logistics of four different kinds of hospitals was examined through a qualitative case study.…”
Section: Logistics Variables For Efficient Supply Chainmentioning
confidence: 99%
“…A cross-section of some key logistics key variables or factors are presented in Table II. [23], examined how modularity is used for enabling value creation in managing healthcare logistics services. They applied materials logistics of four different kinds of hospitals was examined through a qualitative case study.…”
Section: Logistics Variables For Efficient Supply Chainmentioning
confidence: 99%
“…Typically the actor who is to receive goods into internal supply chain is the hospital's central warehouse, which is traditionally located inside a hospital to ensure fast supplies and availability (Rivard-Royer et al, 2002). Furthermore, a central warehouse may also be closely connected to other support services, such as a pharmacy service (Volland et al, 2017), food supply, instrument maintenance, a laundry service and an assistive device service (Pohjosenperä et al, 2018). The central warehouse regularly delivers to the point-of-use inventories that are typically located close to patient care locations (Bijvank and Vis, 2012).…”
Section: Value Co-creation In Health-care Materials Logisticsmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/ 1359-8546.htm There have been a number of reported documents and articles suggesting initiatives that can potentially improve the PSC. Reviewing the academic literature, scholars investigating the PSC found that certain benefits can be claimed, including effective inventory control (Bam et al, 2017;Pereira et al, 2014), improved information reliability (Chowdhury et al, 2016), firm innovativeness (Papalexi et al, 2015;Gölgeci and Ponomarov, 2015), organisational performance (Birkie et al, 2017), reduction of pharmaceutical waste and increased quality of healthcare services, (Pohjosenperä et al, 2018;Volland et al, 2017;Breen and Xie, 2015). Similarly, to the treatise within the academic literature, from a practical perspective, healthcare institutes such as the Department of Health (UK) and the national organisation for medicines (Greece) have outlined a series of guidelines aiming to determine how best practices can be adopted to enhance the delivery process (Department of Health (DoH), 2014; NOfM, 2016).…”
Section: Introductionmentioning
confidence: 99%